1997
DOI: 10.1002/mds.870120203
|View full text |Cite
|
Sign up to set email alerts
|

Multiple system atrophy: A review of 203 pathologically proven cases

Abstract: We report the clinicopathological features of 203 cases of pathologically proven multiple system atrophy (MSA) from 108 publications up to February 1995. The majority of patients showed symptoms in their early fifties, and men were more commonly affected than women (ratio of 1.3:1). Most patients suffered from some degree of autonomic failure (74%). Parkinsonism was the most common motor disorder (87%), followed by cerebellar ataxia (54%) and pyramidal signs (49%). The response to levodopa was poor in most pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

40
507
8
16

Year Published

1997
1997
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 743 publications
(571 citation statements)
references
References 99 publications
40
507
8
16
Order By: Relevance
“…In this series, the frequency of neruogenic bladder at an early stage and impotence was relatively low compared with several previous reports [12,14]. However, this result may have been biased because it was determined by asking questions and by retrospective review of each patient's medical record.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…In this series, the frequency of neruogenic bladder at an early stage and impotence was relatively low compared with several previous reports [12,14]. However, this result may have been biased because it was determined by asking questions and by retrospective review of each patient's medical record.…”
Section: Discussioncontrasting
confidence: 53%
“…Other disorders associated with parkinsonism, such as Parkinson's disease with autonomic failure, progressive supranuclear palsy (PSP), and diffuse Lewy body disease (DLBD), may often be misdiagnosed as MSA-P [7,8,9,10,11,12]. A neuropathological study showed that Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…23 On the other hand, in MSA degeneration of the olivopontocerebellum (the transverse pontineˆbers and pontine neurons), striatonigral and autonomic systems are seen; however, degeneration of the gray matter around the aqua duct and superior colliculus does not occur. 26,27 The midbrain usually shrinks not only in PSP, but also in MSA. However, in the present study, the lateral margin of the midbrain in four of theˆve PSP patients was concave (the morning glory sign) and that of almost all patients with MSA remained convex.…”
Section: Discussionmentioning
confidence: 99%
“…However, the differential diagnosis of parkinsonism continues to be challenging with a high misdiagnosis rate, particularly in the early stage [6], because parkinsonian patients show similar symptoms and specific symptoms do not appear in early stage [7]. It is of importance to make an accurate differential diagnosis of parkinsonism to decide on treatment regimens [8], provide a prognosis [9], investigate etiology and pathogenesis, and to develop new therapeutic strategies [10].…”
Section: Introductionmentioning
confidence: 99%